Synthesis and optical properties of a new triphenylamine-p-phenylenevinylene-small molecule with applications in high open-circuit voltage organic solar cells1. (24th September 2015) - Meira, Rui; Costa, Pedro M. M.; Di Paolo, Roberto E.; Morgado, Jorge; Alcácer, Luís; Bastos, João P.; Cheyns, David; Charas, Ana
<x xml:space="preserve">Abstract</x> Fluorescence quenching studies enabled us to preview applications of a new small molecule as electron-donor in OSCs. Planar heterojunction cells are also shown.